Determinants of Chicken Market Participation Decisions by Smallholder Farmers in West Gojam Zone, Ethiopia: A Gender Perspective - Giziew, Almaz (Ethiopian Journal of Social Sciences, 2018)
Ethiopia is a country where village chicken plays a dominant role in total chicken production. Chicken production as part of livestock production could be one alternative in generating income for rural households. Although some researchers studied chicken in Ethiopia, they asses and examine merely the production practices of chicken like adoption, feeding and variety. This indicates that there is huge knowledge gap regarding the determinants of chicken Market Participation Decisions by Smallholder farmers in Ethiopia. Thus, this study identified determinant factors affecting chicken market participation decisions by smallholder farmers in Mecha and Bahir Dar Zuria districts, Ethiopia. The data used in this study were collected from 154 male and 46 female headed households who were selected via multistage sampling technique from four kebeles of the district. The data were analyzed using t-test, chi-square. Probit and Heckman two-stage selection were estimated to identify the determinants of chicken marketing participation-decision in Female-Headed Households (FHH) and Male-Headed Households (MHH). The probit model results indicate that distance from the nearest market, number of chicken owned, breed type and getting extension service influenced FHH farmers’ decision to participate in marketing significantly. Experience of chicken production, market information, use of credit, and income from non-farm activity influenced MHHs’ decision to participate in marketing. Therefore, in order to realize the country’s long-term vision of food security and achieve agricultural and rural development, all the determinants of participation-decision and value of chicken sales should be considered by policy makers as a new insight for intervention measures.